Effect of unbalanced overloading on the cornering stability profile of nonholonomic two in-wheel compact electric vehicle - Baarath, Kunjunni (2020)
The recent development of vehicle technology is shifting towards the autonomous and electric vehicle. Electric vehicle technology has grown to pave a path towards wheel motored electric vehicles (IWMEV). Like conventional internal combustion vehicle, IWMEV are also susceptible to instability which could result in accidents. Accidents are divided into three categories based on the cause, namely vehicle condition, human error and environmental condition. Most accidents that occur are results of human behaviour. Unbalanced overloading is identified as one of the factors that affect the stability of the vehicle thus, leading to accidents. Increasing load on one side of the vehicle moves the position of the centre of gravity leading to an increase in the probability of vehicle instability. Moreover, compared to conventional internal combustion vehicle, IWMEV are considered lightweight vehicle due to the absence of mechanical linkage and engine. This causes IWMEVs to be affected by unbalanced overloading. Therefore, the objective of this research is to identify the effect of unbalanced overloading on the stability profile of the electric vehicle. Thus, a simulation model of an IWMEV is developed by combining the load transfer equation, Dugoff’s tire model, nonlinear vehicle dynamic equation and the DC motor model. The developed model is verified using a compact IWMEV. Then, the model is used to identify the effect of load increase at the left and right side during a sharp right turn. The vehicle is set to run at four different velocities namely 10 km/h, 15 km/h, 20 km/h and 25 km/h. It is observed that the vehicle reaches the Friction Circle Coefficient limit at the front left tire for a 60% right load increase condition. This causes the vehicle to crash. A load stability index named Binary Attribute Stability Indicator (BASI) is proposed to identify the stability of the vehicle at different load distribution. The BASI can help determine the stability level of the vehicle based on lateral acceleration, yaw rate, FCC, and rollover index.